Education on the Threshold of the Third Millennium: Challenge, Mission, and Adventure - Pittau, SJ, Guiseppe (Catholic Education: A Journal of Inquiry and Practice, 2000)
On May 18, 1999, the newly appointed Secretary of the Congregation for Catholic Education, the Vatican office for Catholic schools, universities, and seminaries, addressed a gathering of Catholic school administrators at Fordham University. The Most Reverend Giuseppe Pittau, S.J., was invited to deliver an address to the Fifth Annual School Executive Leadership Dinner. Archbishop Pittau brings a wealth of experience to his new position at the Vatican. In his role as Secretary, he shares responsibility for some 900 Catholic colleges and universities, over 3550 seminaries, and tens of thousands of Catholic schools. In his address, Pittau offers a synthesis of current challenges facing Catholic schools and highlights the critical role of parents, teachers, administrators, and the community in the education of children.